An assessment of rubber dam usage amongst specialists in paediatric dentistry practising within the UK - FRANCESCA SOLDANI & JENNIFER FOLEY (IAPD and Blackwell, 2007)
Rubber dam is recommended by the British Society of Paediatric Dentistry (BSPD) for various restorative and endodontic procedures. To date, there has been no report of actual usage of rubber dam within the speciality of paediatric dentistry